Strengthening Students' Religious Nationalism through Religious Moderation Programs in Islamic Higher Education - Suryati Suryati; Ahmad Suradi; Adisel Adisel; Nazarmanto Nazarmanto (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
This study addresses a gap in research on religious moderation and nationalism, which has largely remained descriptive and has insufficiently examined how religious nationalism develops through educational processes or influences students’ commitment to the nation. In particular, limited attention has been given to the interaction of cognitive, affective, and behavioral dimensions within religious moderation programs in Islamic higher education. This research employs a qualitative case study approach conducted at an Islamic higher education institution. Data were collected through in-depth interviews with lecturers, program coordinators, and students, as well as participant observation of learning activities and campus programs related to religious moderation. Purposive sampling was used to select informants directly involved in the program. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, with triangulation applied to ensure validity. The findings indicate that religious moderation programs significantly strengthen students’ religious nationalism through a multidimensional process of value internalization, attitude transformation, and behavioral actualization. Students develop an integrative understanding of religion and nationalism that fosters inclusive, tolerant attitudes, active civic engagement, and participation in national and social activities. Religious nationalism also enhances ideological resilience against radicalism and reinforces commitment to national unity. This study contributes to the literature by offering an integrative framework that explains how cognitive, affective, and behavioral dimensions interact in shaping religious nationalism among students. Its novelty lies in conceptualizing religious nationalism as a multidimensional outcome of religious moderation programs. The findings further suggest that policymakers and higher education institutions should strengthen dialogical, contextual, and experiential learning strategies to promote social cohesion, civic responsibility, and resilience against extremist ideologies.